2006
DOI: 10.1038/nm1418
|View full text |Cite|
|
Sign up to set email alerts
|

Altered neuregulin 1–erbB4 signaling contributes to NMDA> receptor hypofunction in schizophrenia

Abstract: Recent molecular genetics studies implicate neuregulin 1 (NRG1) and its receptor erbB in the pathophysiology of schizophrenia. Among NRG1 receptors, erbB4 is of particular interest because of its crucial roles in neurodevelopment and in the modulation of N-methyl-D-aspartate (NMDA) receptor signaling. Here, using a new postmortem tissue-stimulation approach, we show a marked increase in NRG1-induced activation of erbB4 in the prefrontal cortex in schizophrenia. Levels of NRG1 and erbB4, however, did not differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
416
2
14

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 530 publications
(461 citation statements)
references
References 27 publications
23
416
2
14
Order By: Relevance
“…However, isoform-specific increases in PFC NRG1 and ErbB4 mRNA expression have also been observed in these patients (Hashimoto et al 2004;Law et al 2006;Law et al 2007;Silberberg et al 2006). Thus, it appears changes in brain NRG1 and/or ErbB4 levels may play roles in schizophrenia, although altered ErbB4 activation with no significant changes in NRG1 and ErbB4 protein quantities has recently been shown in patient brains (Hahn et al 2006).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, isoform-specific increases in PFC NRG1 and ErbB4 mRNA expression have also been observed in these patients (Hashimoto et al 2004;Law et al 2006;Law et al 2007;Silberberg et al 2006). Thus, it appears changes in brain NRG1 and/or ErbB4 levels may play roles in schizophrenia, although altered ErbB4 activation with no significant changes in NRG1 and ErbB4 protein quantities has recently been shown in patient brains (Hahn et al 2006).…”
Section: Introductionmentioning
confidence: 85%
“…Hahn et al (2006) examined PFC NRG1 and ErbB4 protein in an aged schizophrenia population, while Bertram et al (2007) analyzed PFC NRG1α protein though NRG1β may be more abundant in brain (Meyer and Birchmeier 1994;Wen et al 1994). The present research sought to determine whether previously reported schizophrenia-associated alterations in PFC NRG1 and ErbB4 mRNA levels could be observed at the protein level in PFC tissues from the Stanley Consortium.…”
Section: Introductionmentioning
confidence: 99%
“…However, if it can be demonstrated that RPTPb antagonizes NRG1-ERBB4 signaling in vivo, then we would predict that reduced functioning of RPTPb would result in a phenotype like that of enhanced NRG1-ERBB4 signaling. 22 This would provide a potential mechanism by which PTPRZ1/RPTPb could be involved in the molecular basis of schizophrenia. PTPRZ1 gene products are expressed mainly in the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that investigated neuregulin stimulation of ERBB4 in slices of prefrontal cortex from control and schizophrenic subjects demonstrated enhanced activation of ERBB4 by neuregulin in schizophrenia. 22 Finally, mouse models with disruptions in NRG1-ERBB4 signaling appear to capture some of the behavioral phenotypes associated with schizophrenia, and in certain cases these altered behaviors can be ameliorated by antipsychotics. 1,[23][24][25] Altogether, the data support a role for abnormal NRG1-ERB signaling in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, neuregulin-1-ErbB4 signaling has also been implicated in the pathogenesis of schizophrenia based on association between neuregulin-1 polymorphisms and the disease in some populations [143][144][145]. Supporting this genetic association, increased neuregulin-1-dependent ErbB4 signaling is seen in the prefrontal cortex of the schizophrenic brain and is associated with decreased activity of the NMDA receptor, possibly contributing to the pathogenesis of schizophrenia [146].…”
Section: Erbb Members In Diseasementioning
confidence: 97%